2009
DOI: 10.1002/eej.20861
|View full text |Cite
|
Sign up to set email alerts
|

Remote surface modification of plastics by atmospheric barrier discharge

Abstract: SUMMARYThe surface modification by atmospheric pressure barrier discharge is effective in the improvement of adhesion performance of plastics. Remote plasma processing has several advantages over direct plasma processing. It is free from the problem of surface damage and charge accumulation and has larger freedom of setup of the system. However, it is necessary to improve the processing performances such as range of remote processing distance, reduction of contact angle, and so on.In this paper, we have invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…31) The present study focuses on the effects of Ar and O which were clearly indicated. Especially, ground state O with a short lifetime (∼10 −5 s) 32) can react with ambient O 2 to form ozone (O 3 ). The chemical path of this reaction is well-known as 33) O O O .…”
Section: Resultsmentioning
confidence: 99%
“…31) The present study focuses on the effects of Ar and O which were clearly indicated. Especially, ground state O with a short lifetime (∼10 −5 s) 32) can react with ambient O 2 to form ozone (O 3 ). The chemical path of this reaction is well-known as 33) O O O .…”
Section: Resultsmentioning
confidence: 99%
“…Hyeop et al 2007, Y. Yanagisawa et al 2009, C. E. Nwankire et al 2010 Numéricamente se puede ver que, utilizando agua como líquido de contacto, el valor obtenido del ángulo presenta un valor mínimo de 43,50º para una velocidad de pasada de 100 mm/s. Como el ángulo de contacto del agua sobre el PP sin tratar es de 103,74º, esto supone una reducción de alrededor del 58%, respecto al valor inicial.…”
unclassified